Constructions of urban space - Hutchinson, Ray. (Stamford, Conn. : JAI Press, 2000)
Urban space has emerged as the central organizing construct in studies of the post-modern metropolis. Contributors to this volume write on how urban space is used and contested by different social groups, how urban space is transformed by the changing economic relationships manifested in the new world order, and how urban space is defined by those who use and study it.
Introduction to constructions of urban space / Ray Hutchison -- Public spaces: a comparative discussion of the criteria for public space / Lewis W. Dijkstra -- New urban spaces and cultural representations: social imagineries, social-physical space, and homelessness / Talmadge Wright -- Spying on an eyesore: space, place, and urban decay / Paul Draus with Cornelius Howard -- Conflict, space, and identity: two cases, one process / Scott Swearington Cecilia Orellana-Rojas -- Spatial anarchy and urban utopias: public art controversies and urban space / Kim M. Babon -- Speaking the city: skateboarding subculture and recompositions of the urban realm / Iain Borden -- Representations of space and urban planning in a post-World War II U.S. city / Kevin Fox Gotham -- Toward an urban sociology of mega-events / Harry H. Hiller -- Tourism and the revitalization of Harlem / Lily M. Hoffman -- Distinguishing metropolises: the production of urban imagery / William G. Holt, III -- Red hook: the paradoxes of poverty and place in Brooklyn / Philip Kasinitz -- Gendered space and women's community work / Judith N. DeSena.
Description based on print version record.
Keywords: Sociology, Urban; Public spaces; City planning; Space (Architecture); Urban geography; Urban policy; Social research & statistics; Urban communities; Social Science -- Sociology -- General